Breast milk expression for premature infant in the neonatal intensive care unit: A review of mothers’ perceptions - Siti Azuna, Abu Bakar; Siti Mariam, Muda; Siti Roshaidai, Mohd Arifin; Shareena, Ishak (2019)
Objective: To identify the existing literature on mothers’ perception towards the impact of expressing breast milk for their premature infant in the neonatal intensive care unit. Method: Guided by the PRISMA Statement review checklist, a systematic review of the Scopus and Web of Science database has identified 10 related studies. The articles were assessed and analysed after evaluated using The Joanna Briggs Institute Critical Appraisal tools (JBI). Thematic analysis was obtained after using Nvivo software as a tool for data analysis by author. Result: Further review of these articles resulted in four main themes— maternal changes during expressing breast milk, pumping challenges and impact of motivation factors to initiating lactation. Conclusion: Expressing breast milk should be recognized as an important way to restructure motherhood with a preterm infant in NICU. However, maintaining expressed breast milk during preterm infants’ treatment period in NICU may increase stress and difficulties for some mothers. Some recommendations are emphasized in relation to the need for more qualitative studies in this issue, which is to have a specific and standard systematic review method for guide research synthesis in context of climate change adaptation.